POSHAN’s abstract digest on maternal and child nutrition research – Issue 21 - Avula, Rasmi (International Food Policy Research Institute, 2018)
This issue of Abstract Digest presents two breakthrough studies that take a critical look at the association of water, sanitation, and handwashing (WASH) interventions with nutrition and a systematic review on enteric dysfunction and child stunting. Other interesting studies include those related to the design, cost and other program elements pertaining to diets for maternal and child health.